Relative performance of six Hevea brasiliensis clones during two yielding regimes in Tripura - Priyadarshan P M; Dey S K; Sasikumar S; Sudhasowmyalatha M K; Varghese Y A (Indian Journal of Natural Rubber Research, 1998)
Six oriental Hevea clones of Indian (RRII 208), Malaysian (RRIM 600), Indonesian (PR 107) and Chinese (SCAT88-13, SCAT93-114, Haiken 1) origin were investigated for their performance under two yielding regimes (Regime I = April to September; Regime II = October to January). Regression analysis revealed SCATC 93-114, PR 107 and RRII 208 with the least regression coefficients to be the stable clones and Haiken 1 to be least consistent over the regimes. Though SCATC 93-114 and PR 107 showed a lower regression coefficient, their respective mean yield was low making them less desirable for the tested environment. Comparatively higher contribution was rendered by RRII 208 with a low yield depression (43.8;) during Regime I ensuring higher returns from the stand. Clones SCATC 88-13 and Haiken 1, though not consistent in yield over the regimes, were on par with RRIM 600 with respect to annual mean yield. This study identified three clones, RRII 208, SCATC 88-13 and Haiken 1 as potential ones for on-farm evaluation in Tripura.
Keywords: Girth increment; Girth increment; Hevea; Hevea; Yield depression; Yield depression; Yielding regime; Yielding regime